The Effect of Servant Leadership and Loyalty on Employee Performance at Khairu Ummah Syariah Service Cooperative - Imam Akbari; Furqon Syarief Hidayatulloh; Amiruddin Saleh (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the influence of servant leadership on employee performance, with employee loyalty as a mediating variable, at Koperasi Jasa Syariah Khairu Ummah. Based on data analysis and structural model testing, several key findings were identified. First, servant leadership has a positive and significant effect on employee loyalty, indicating that a leadership style prioritizing employee needs, support, and empathy enhances emotional attachment and commitment to the organization. Second, employee loyalty positively and significantly influences employee performance, suggesting that loyal employees are more motivated and likely to perform better. Third, servant leadership does not directly affect employee performance, implying the presence of a mediating variable. Finally, employee loyalty is proven to mediate the relationship between servant leadership and employee performance, meaning that effective implementation of servant leadership increases loyalty, which in turn improves performance. Overall, the findings emphasize the crucial role of servant leadership in fostering employee loyalty as a foundation for enhancing performance, especially in value-based, sharia-oriented organizations.